KAJIAN OPTIMALISASI RUTE PENGANGKUTAN SAMPAH DI KOTA PONTIANAK - Muhardi, Zeldi (Fakultas Teknik Universitas Tanjungpura, 2015)
Pontianak city is the largest city and also the capital city of West Kalimantan. Along with the rapid development in Pontianak City, the city is now facing waste management issue due to waste disposal and transport which require serious attention. The fact showed that waste is not totally collected and transported. Moreover, there are still many illegal waste disposal sites which have not been handled by Cleaning and Landscaping Agency. Waste management issue seen from the disposal of waste to river, canal or empty land, causing only a small number of transported waste to the landfill. In addition, lack of human resources, financing as well as facilities in waste management are not in accordance with the waste produced by Pontianak people